Information and communication technology in interior design - Jassim Hamid, Reham; Lafta, Rajae Saadi (Al-Adab Journal, 2020)
In view of the technical and technological progress that has become at the present time a major reason for changing lifestyles and interacting with internal spaces, which led to the development of standards of living for the better, and with the clarity of the role of information and communications technology and the abundance of work on them, it helped to overcome many difficulties, thus changing the speed in work to keep pace with this. The vast amount of development and openness of information and determining how to benefit from it and direct it in a way that benefits the internal spaces and the users of these spaces as well to facilitate the work of the designer on these spaces